Islamic Banking and Financial Crisis - Habib Ahmed, Mehmet Asutay, and Rodney Wilson (Edinburgh University Press, 2013)
Do Islamic fi nancial institutions perform better than their conventional counterparts during periods of fi nancial stress? To what extent do systems for managing risk have to be adapted for Islamic fi nancial institutions given the unique characteristics of their assets and liabilities and given the need for SharÄ«Ê¿ah compliance? The eleven contributors to this book address these issues, which have come to prominence since the global fi nancial crisis of 2008 and the subsequent recession. The study explores the challenges for Islamic fi nancial institutions in an international system where banks under Basel III are required to have more capital and liquidity to deal with future shocks. Governance issues are also examined, as these infl uence client and investor perceptions and ultimately have implications for institutional stability and sustainability. The book is an outcome of a conference organised by the Islamic Research and Training Institute of the Islamic Development Bank Group and Durham University, both of which have been centres for research in Islamic fi nance for over three decades. As the Islamic fi nance industry has grown it has inevitably faced greater challenges, the most recent of which was the global fi nancial crisis.